EXCELLENCE OF DESIRABLE COMMERCIAL ATTRIBUTES IN ASPER SP OF WHITE MASTER CULTIVAR USING VEGETABLE GROWTH REGUTATORS - FERRONATO, Marlene de Lurdes (Scientia Agraria, 2001)
The ornamental plantss industry is constantly searching for improved cultivars. Market for aster (Aster sp cv White Master) has grown, steadily during the last years, increasing the importance of this plant in the industry. This growing interest is due to the uniformity of the asters flowers and also to the possibility of growing this species throughout the year. Number of flowers, branch length and fresh weight, and shelf life of cut flowers are major attributes contributing to their aesthetic quality, marketability and price. In an attempt to improve these attributes, we treated plants or cut flowers of aster with chemicals known to stimulate branching and to delay senescence. The experiments were carried out in a green-house (Departamento de Fitotecnia e Fitossatjitarisxno da Universidade Federal do Paraná) in a completely randomized design. Aminoethoxyvynilglycine (AVG) at 0, 150, 300 and 600 µM, followed by immersion 1 mM silver thiosulfate (STS), was sprayed on whole plants. WhoIe plants were also sprayed with ProlaminTM (benzyladenine+GA4/7) at 0, 250, 500 and 1000 mg.L-1, followed by immersion in 200 µM STS for 60 minutes. Aster branches were immersed in 0, 200 (30 or 60 minutes) and 1.000 µM (30 minutes) STS, as well. Excised flowers were treated with 0, 100 or 200 µL.L-1 of 1-methylcyclopropane (1-MCP). Changes on the number of flowers, as well as their appearance (open, closed or wilted), branch length and fresh weight, and the time course of flowers presenting necrotic areas were recorded. Plants treated with 300 µM AVG presented a significant delay (p=5%) on flower wilting, compared to the untreated plants (0 µM AVG). Branches imnmersed in 1.000 µM STS for 30 minutes or sprayed with 250 or 500 mg.L-1 ProlaminTM also presented delay on flower wilting, being the effect remarkable for ProlaminTM (p=5%). The doses of 100 and 200 µL.L-1 of 1-MCP, were shown not to be able to delay significantly (p=5%) the senescence process in the capitulum (ligulated flowers of the ray and tubulous flowers of the disk) of aster plants. Excised flowers treated with 1-MCP presented delay on the arise of necrotic areas, when compared to the controls (0 µL.L-1 1-MCP). In conclusion, prolongation of shelf life in aster can be achieved by treatments with chemicals known inhibit the ethylene biosynthesis (AVG) or signal transduction pathway (STS), or to inhibit organ senescence (ProlaminTM).